تيمة الأنا والآخر في رواية صياد الملائكة لهدرا جرجس - حورية, بكوش (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة إلى الكشف عن طبيعة الصراع بين الأنا و الآخر ؛ الأنا المسيحي والآخر المسلم الذي يعايشه في صعيد مصر . حيث طبيعة العلاقة متوترة . وعبر أحداث متسارعة وفي حيز زمني ضيق تظهر تفاصيل الصراع الدائر بينهما وكيف أنّ الكنيسة والدولة تعمقان الفتنة . اهتمت الدراسة ببنية الشخصيات للإجابة من خلالها عن سؤال محوري هو: كيف يعكس العمل الفني في رواية صياد الملاكة لهدرا جرجس صورة المسلم في مرايا المسيحي المبدع . وما الحيل الفنيّة التي وظفها الروائي لتمرير وحسم هذا الصراع لصالحه ؟. Abstract: This study aims to reveal the nature of the conflict between the ego and the other; the Christian ego and the Muslim other who live with each other in Upper Egypt, where the nature of the relationship is tense. In addition, through the rapid events and in a narrow time space, the details of the conflict between them appear and how the Church and the state deepen the strife. The study focused on the structure of the characters to answer a central question: How does the artwork reflect in the novel of صياد الملاكة (the Angels’ Hunter) by Hadra Gerges, the image of the Muslim in the mirrors of the creative Christian. What were the technical tricks the novelist used to pass and resolve this conflict in his favor?
مقال
Keywords: المسلم – المسيحي–صياد الملائكة – الأنا - الآخر; Muslim - Christian - The Angels’Hunter's- the ego- the other.